ADMINISTRATION, MANAGEMENT AND MODELING OF ACCOUNTS RECEIVABLE POLICIES IN SMEs. CASE OF SANTO DOMINGO - Ugando Peñate, Mikel; Sabando García, Ángel Ramón; Miranda Reyes, Roger Steven; Andrade Espinoza, Yajaira Joseline (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The purpose of this research is to present the relevance of a proper administration and management of accounts receivable policies in the company DISMAREX S.C through the financial modeling applied. It is intended to create a culture of managing accounts receivable by establishing a scientifically structured and efficient collection management policy. To this end, a financial analysis and the application of administration and modeling techniques related to collections (accounts receivable, bad accounts and sales levels) will be developed. Through a mixed methodological research approach, the guidelines offered for the optimization of accounts receivable in Cuban companies. Particularly as results, the accelerated growth of inventory and accounts receivable cycles and accelerated decrease in accounts payable were evidenced, with little control over sales, which directly affected the sustainability of the company’s financial management. Given the problem that arises in the organization due to the growth of delinquencies in the portfolio, it is urgently sought to promote guidelines aimed at collection policies that lead to the improvement of competitiveness and opportunity in carrying out its commercial activities.